Effect of pollution on physical and chemical water data: a multivariate statistical analysis - Fonseca, Dangelys (2023)
This study aimed to show the importance and functionality of the tools of multivariate statistics in the environmental area, and more specifically on 13 water collection points of the Subaé River in the municipality of Feira de Santana, Bahia, an important Industrial Pole in the region, carried out with 3 samplings. To achieve this objective, applied research of exploratory nature and quantitative approach was carried out. As method and technical procedures were adopted, respectively, the bibliographic review, and a case study. As a contribution of this research, it is pointed out the holistic view of opportunities to carry out new research on the subject in question with the tools presented.